(untitled) (Al-Mansour Journal, 2025)
This research Addresses civil wars and liberation wars. Because many countries hglsjulvm, when the colonized peoples were exploited for their human and material resources, and made these countries weak; and back ward in all aspects. This is a result of the colonialism of western countries, especially British colonialism, and the subsequent woes on the colonized counties. one of the Civil wars, the American Civil war and the Spanish Civil war, but for the struggle of the peoples and national consciousness, this kind of struggle against foreign colonizers has become a sacred national duty. which stirred the conscience of these Countries to be exposed to injustice, tyranny and oppression. National liberation movements became the slogan of this resistance, and the best evidence of this is the Algerian people’s resistance to the French Occupation and their forced evacuation from Algeria and the achievement of it.